Increasing levels of cassava wastewater in the production of papaya formosa seedlings - Pereira, Ramón Yuri Ferreira; Araújo, Thalles Eduardo Rodrigues de; Oliveira, Paula Sara Teixeira de; Silva, Fabíola Luzia de Sousa; Nunes, Rafaela Leopoldina Silva; Cordeiro, Kleber Veras; Silva-Matos, Raissa Rachel Salustriano da (Comunicata Scientiae, 2024)
Cassava wastewater (CWW) is rich in nutrients for plants, presenting great potential as an alternative fertilizer. However, this waste is incorrectly disposed of in the environment, which causes environmental problems. The objective was to evaluate the influence of increasing doses of CWW on the production of formosa papaya seedlings. The experiment was installed in a greenhouse from October 22 to December 5, 2019, in which a completely randomized design was applied with 4 treatments of different levels of CWW with 0 ml L-1, 6.25 ml L-1, 12.5 ml L-1, 25 ml L-1, where each treatment contained 4 replicates of 4 seedlings. Biometric parameters were evaluated to identify the effects of CWW on initial papaya growth. Data were subjected to analysis of variance by F test, and data were explored through regression analysis. Significance was found for root length (RL) and root diameter (RD). The other biometric parameters did not respond to the tested doses of CWW. The tested doses reduced the RL and the DR had the best performance with the dose of 13.5 ml L-1. 13.5 ml L-1 of cassava effluents is recommended for better development of DR. In general, this residue has an inhibitory effect on the initial growth of the papaya tree and is not recommended for the production of seedlings of this species.